Pengawasan dan Penyidikan Otoritas Jasa Keuangan terhadap Koperasi yang Melakukan Kegiatan Usaha Perbankan Tanpa Izin - Mairul (Jimly School of Law and Government, 2023)
Cooperatives are legal entities established with the aim of improving the welfare of members based on Law No. 25 of 1992 on Cooperatives. As time goes by, there are many cooperative practices that carry out banking business without license, such as deposits or term savings. Not a few cooperatives end up going bankrupt or being reported for fraud because they are unable to pay interest and disburse deposit funds from their members or non-members. The practice of banking activities without a license carried out by cooperatives clearly violates Article 46Pparagraph (1) of Law No. 10 of 1998 on Amendments to Law No. 7 of 1992 on Banking. The rise of banking practices without license carried out by cooperatives is partly due to weak supervision of cooperatives by the government which should be carried out by the Ministry of Cooperatives and Small and Medium Enterprises. Therefore, referring to Article 44B Paragraph (3) of Law No. 4 of 2023 on Development and Strengthening of the Financial Sector jo. Article 6 of Law No. 21 of 2011 on the Indonesia Financial Services Authority (OJK), the institution that has the right to supervise cooperatives operating in the financial services sector is the Indonesia Financial Services Authority (OJK).